Intrinsic and phasic entrepreneurial alertness for opportunity recognition : An analysis of Asian entrepreneurs - Wang, Fan; Singh, Nitish; Khan, Zaheer (Springer Nature, 2024)
Entrepreneurial alertness (EA) is pivotal in opportunity recognition, yet the origins and processes underlying EA remain elusive. Drawing upon key insights from the neuroscience and entrepreneurship streams of literature, our study classifies EA into intrinsic and phasic components to delve into the entrepreneurial opportunity recognition process. Intrinsic EA—a self-initiated top-down control mechanism—continuously processes information to generate unconstrained associations from entrepreneurial schemata. As gatekeepers, intrinsic EA pre-processes external stimuli and internal thoughts, aiming to produce novel insights that may manifest as potential opportunities or threats. This triggers phasic EA, a short-term, bottom-up process with a selective focus on the insights. Phasic EA employs experiments to assess the attractiveness of first-person opportunities, refining entrepreneurial schemata. Utilizing 52 video interviews of 11 mainland Chinese, Taiwanese, Singaporean, and Indian entrepreneurs, our research distinguishes between intrinsic and phasic EA, delves into their origins, and presents a unified framework to elucidate their respective roles in entrepreneurial opportunity recognition.
Keywords: Entrepreneurial alertness; Intrinsic EA; Phasic EA; Schemata; Entrepreneurial ventures; Asian Entrepreneurs